Serious and Violent Offender Reentry Initiative (SVORI) Multi-site Impact Evaluation, 2004-2011 (United States) - Lattimore, Pamela K. ([Verlag nicht ermittelbar], 2011)
The Serious and Violent Offender Reentry Initiative (SVORI) funded agencies to develop programs to improve criminal justice, employment, education, health, and housing outcomes for released prisoners. SVORI was a goal-oriented initiative that specified outcomes that should be achieved by programs that were developed locally. The original Multi-site Evaluation of SVORI funded under NIJ grant 2004-RE-CX-0002 included a quasi-experimental impact evaluation to determine the effectiveness of programming. Specifically, the purpose of the impact evaluation was to determine whether individuals who participated in enhanced reentry programming, as measured by their enrollment in SVORI programs, had improved post-release outcomes than comparable individuals who did not participate in SVORI programming. Impact evaluation data collection for both SVORI and non-SVORI participants consisted of four waves of in-person, computer-assisted interviews and oral swab drug tests conducted in conjunction with two of the follow-up interviews. The research team collected data on a total of 2,391 individuals including 1,697 adult males (Part 1), 357 adult females (Part 2), and 337 juvenile males (Part 3). As part of the impact evaluation, experienced RTI field interviewers conducted pre-release interviews with offenders approximately 30 days before release from prison and a series of follow-up interviews at 3, 9, and 15 months post-release. These data provided information on criminal history and recidivism occurring by December 31, 2007. The Adult Males Data (Part 1), Adult Females Data (Part 2), and the Juvenile Males Data (Part 3) each contain the same 5,566 variables from the 3 waves of offender interviews, 10 drug test lab results variables, and 3 weight variables. (Note: Some interview questions were only asked of adults, and other questions were only asked of juveniles.) Offender interview variables include demographics, housing, employment, education, military experience, family background, peer relationships, program operations and services, physical and mental health, substance abuse, crime and delinquency, and attitudes toward those topics. Under NIJ Grant 2009-IJ-CX-0010, the original Multi-site Evaluation of SVORI data were updated in order to examine the questions of, "What works, for whom, and for how long?" This included follow-up interview questions of those previously (and currently still) incarcerated. New variables derived from data collected under the original SVORI impact evaluation between 2004 and 2007 were also added to Part 3. Part one included an additional 100 variables, part two an additional 102 variables and part 3 an additional 99 variables.